HVAC System Energy Retrofit for a University Lecture Room Considering Private and Public Interests - Diana D’Agostino; Federico Minelli; Francesco Minichiello (Energies)
The operation of Heating Ventilation and Air Conditioning (HVAC) systems in densely occupied spaces results in considerable energy consumption. In the post-pandemic context, stricter indoor air quality standards and higher ventilation rates further increase energy demand. In this paper, the energy retrofit of a partial recirculation all-air HVAC system serving a university lecture room located in Southern Italy is analyzed. Multi-Objective Optimization (MOO) and Multi-Criteria Decision-Making (MCDM) approaches are used to find optimal design alternatives and rank these considering two different decision-makers, i.e., public and private stakeholders. Among the Pareto solutions obtained from optimization, the optimal alternative is identified, encompassing three Key Performance Indicators and using a new robust MCDM approach based on four methods, i.e., TOPSIS, VIKOR, WASPAS, and MULTIMOORA. The results show that, in the post-pandemic era, baseline retrofit scenarios for infection reduction that do not involve the introduction of demand control ventilation strategies cause energy consumption to increase from negligible values up to 59%. On the contrary, baseline retrofit scenarios involving demand control ventilation strategies cause energy consumption to decrease between 5% and 38%. The findings offer valuable guidance for HVAC system retrofits in higher education and similar buildings, emphasizing the potential to balance occupant health, energy efficiency, and cost reduction. The results also highlight significant CO2 reductions and minimal impacts on thermal comfort, showcasing the potential for substantial energy savings through targeted retrofits.